2016
DOI: 10.21608/jappmu.2016.48746
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Conventional and Non-Conventional Extenders on Rams Semen Quality During Storage at 5ºC

Abstract: The aim of the present study was to define the effect of different extender components (as conventional and nonconventional extenders) on rams' semen quality during storage at 5ºC for up to 6 days. Fertility rates of the extended ram spermatozoa stored at 5ºC for up one day were also studied. Four Rahmani rams were used to collect pooled ejaculates by artificial vagina. Semen was collected, evaluated and extended with five extenders included conventional and non-conventional extender ingredients. The conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…Advancement of storage time for up to 48 hours in extender types can depressed significantly (P<0.05) the percentage of advanced sperm motility. These results are similar to that reported in stallion (Santos, 2014), bull (El-Sisy et al, 2016), rabbit (El-Seadawy et al, 2017) and ram (Khalifa and Khalil, 2016). Decreasing progressive motility attainted to gradual depletion of nutrients (Gibb and Aitken, 2016), enhance productive of free radical (Acharya et al, 2016) and inhibit of fructolysis and respiration spermatozoa (Gündoğan et al, 2003).…”
Section: Discussionsupporting
confidence: 90%
“…Advancement of storage time for up to 48 hours in extender types can depressed significantly (P<0.05) the percentage of advanced sperm motility. These results are similar to that reported in stallion (Santos, 2014), bull (El-Sisy et al, 2016), rabbit (El-Seadawy et al, 2017) and ram (Khalifa and Khalil, 2016). Decreasing progressive motility attainted to gradual depletion of nutrients (Gibb and Aitken, 2016), enhance productive of free radical (Acharya et al, 2016) and inhibit of fructolysis and respiration spermatozoa (Gündoğan et al, 2003).…”
Section: Discussionsupporting
confidence: 90%
“…This further corroborates the report of Mahiddine & Kim (2021), that post-thaw parameters of cryopreserved sperm are poorer than those of fresh sperm. The sperm motility recorded in this study are similar to that reported in rams (Khalifa & Khalil 2016). The decreasing sperm motility observed was attributed to depletion of nutrients (Gibb & Aitken 2016), which inhibit fructolysis and respiration of sperm cells (Gündoğan et al, 2003).…”
Section: Resultssupporting
confidence: 87%
“…Our findings postulated that EGD, SLD and CPDA extenders indicated better semen characteristics such as motility, live, normal and intact acrosome than CPD extender maybe had a positive effect on reproductive performance. Confirmation by Khalifa and Khalil (2016) who find out that Tris‐based extender with egg yolk and soybean lecithin has a beneficial effect on chilling characteristics of ram semen extender which lead to the best conception and fertility rates. On the other hand, Mostafa et al.…”
Section: Discussionmentioning
confidence: 66%
“…Our findings postulated that EGD, SLD and CPDA extenders indicated better semen characteristics such as motility, live, normal and intact acrosome than CPD extender maybe had a positive effect on reproductive performance. Confirmation by Khalifa and Khalil (2016) who find out that Tris-based extender with egg yolk and soybean lecithin has a beneficial effect on chilling characteristics of ram semen extender which lead to the best conception It has found been that the best conception rate and fertility rate in EGD and SLD may be attributed to protein in egg yolk (Anzar, Rajapaksha, & Boswall, 2019) and soybean lecithin (Baruah et al, 2019). The lowest conception rate and fertility rate in semen diluted with CPD (without antibiotic) extender could also be due to contamination of handling semen during collection and preservation (Khalifa, Mohamed, & Abdel-Hafez, 2016, 2016b.…”
Section: Fertility Assessmentsmentioning
confidence: 91%
See 1 more Smart Citation